Effectiveness of Electro-Acupuncture on Blood Pressure in Hypertensive Patients in Sanan Village Girimarto Wonogiri - Saputri, Tiara Lusty; Haryanto, Joko Tri; Badri, Sholichan (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Hypertension is the root of various non-communicable diseases that are still a health problem in Indonesia. Acupuncture therapy can reduce systolic and diastolic blood pressure in patients with hypertension. Hypertension generally occurs in the elderly, but some studies show that hypertension can appear since adolescence. The method used is Quasi Experimental Design with a pretest-posttest two-group design. The sample used was 32 research subjects. The sampling technique used was purposive sampling technique. The statistical test used was the Paired T-test. This research was conducted in Sanan Village, Girimarto, Wonogiri Regency, in February-March 2024. From the hypothesis test above using the Paired T-Test test because the research data was normally distributed and homogeneous. The results showed that for the acupuncture therapy Group, the p-value<0.001, which means the p-value <0.05, so Ha is accepted and H₀ is rejected. In the acupuncture therapy Group, p<0.001, which means the p-value <0.050, the results show that electroacupuncture is more effective on blood pressure in hypertensive patients. Conclusion: Electro-acupuncture therapy is effective for high blood pressure in hypertensive patients in Sanan Village Girimarto Wonogiri.